The plausibility of developing a digitised township economy: A study of townships in Cape Town - Tsolekile, Sisanda (University of the Witwatersrand, Johannesburg, 2021)
South Africa has a 91% penetration of smartphones in its adult population, making a plausible case for doing business on digital platforms including mobile apps. In the digital economy, business growth is hinged on the core capabilities of its owners or its human capital, while the customer remains at the centre of how business is conducted. The Covid-19 lockdowns have forced an accelerated adoption of the digital economy by any business that intends to survive. If township businesses participate in the digital economy that places a demand on the businesses to make a shift in their format of customer relationship management. In the case where the business had walk-in customers with face-to-face human interaction, businesses then need to transition their customer engagement efforts into social media networks, and this demands that they upskill and learn new interaction skills to make them effective digital citizens. The study goes on to build a case that reveals how increased internet connectivity in businesses present both growth opportunities as well as novice challenges such as cybersecurity threats. These businesses therefore need to invest in cybersecurity to protect their trade secrets and personal customer data. In the same vein, the government has a role to play to ensure that the economic environment is conducive for conducting business activities. The study also finds that while the government is doing its part in empowering the township population by developing the internet connectivity infrastructure, the same community members who are meant to be beneficiaries of the infrastructure were responsible for destroying it. The study concludes by making recommendations for what a typical township business needs to do to participate in the digital economy. Finally, if the township digital economy were to be plausible, the researcher recommends that all township small businesses should structure themselves as learning businesses incorporating the above-mentioned factors while constantly refreshing their technology and entrepreneurial skills
A research article presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg 2021
Keywords: Township digital economy; eGovernment; Entrepreneurship; Township SMEs; Customer relationship management; UCTD; SDG-8: Decent work and economic growth